Health care experiences and birth outcomes: Results of an Aboriginal birth cohort. Issue 5 (October 2019) - Brown, Stephanie J.; Gartland, Deirdre; Weetra, Donna; Leane, Cathy; Francis, Theresa; Mitchell, Amanda; Glover, Karen
Abstract: Objective: The aim of this study was to investigate the relationship between perceived discrimination in perinatal care and birth outcomes of women giving birth to an Aboriginal baby in South Australia using methods designed to respect Aboriginal culture and communities. Design and setting: Population-based study of women giving birth to Aboriginal infants in South Australia, July 2011–June 2013. Women completed a structured questionnaire with an Aboriginal researcher. Study measures include: standardised measure of perceived discrimination in perinatal care; maternal smoking, cannabis use and exposure to stressful events and social health issues; infant birthweight and gestation. Participants: 344 women (mean age 25, range 15–43 years) living in urban, regional and remote areas of South Australia. Results: Half of women (51%) perceived that they had experienced discrimination or unfair treatment by hospitals or health services providing care during pregnancy and soon after childbirth. Women experiencing three or more stressful events or social health issues were more likely to perceive that care was discriminatory or unfair. Aboriginal women who perceived that they had experienced discrimination in perinatal care were more likely to have a baby with a low birthweight (Adj Odds Ratio 1.9, 95% CI 1.0–3.8) or small for gestational age (Adj Odds Ratio 1.9, 95% CI 1.0–3.5), adjusting for parity, smoking and cannabis use. Conclusions: The study provides evidence of the 'inverse care law'. Aboriginal women most at risk of poor infant health outcomes were the least likely to perceive that they received care well matched to their needs. Building stronger evidence about what works to create cultural safety in perinatal health care is an urgent priority.